Resilience by Teaming in Supply Chains and Networks - Reyes Levalle, Rodrigo (Automation, Collaboration, & E-Services,, 2018)
Real-world supply chains and networks are inherently complex, formed by a large number of self-governing interconnected agents which dynamically update their behavior rules and connections based on context and environment changes. Oftentimes, these complex systems fail, almost inexplicably, due to unforeseen events leading to disruption. Exploration and research of the mechanisms behind the failure of supply chains and networks have revealed that those capable of surviving are not only robust, but resilient. The purpose of this book is to explain the meaning of resilience and its design in the broad context, and with a focus on the design and management of supply chains and supply networks. Written by Dr. Reyes Levalle, an experienced supply chains designer and supply networks engineer, the book is intended for beginners and advanced professionals, students, designers, policy makers, and managers. It is a pioneering effort to base resilience engineering and management on CCT, the collaborative control theory and tools. .